1974
DOI: 10.1037/h0036351
|View full text |Cite
|
Sign up to set email alerts
|

Structure and process in semantic memory: A featural model for semantic decisions.

Abstract: A model is proposed to account for recent findings on the time needed to decide that a test instance is a member of a target semantic category. It is assumed that the meaning of a lexical term can be represented by semantic features. Some of these features are essential or defining aspects of a word's meaning (defining features), while others are more accidental or characteristic aspects (characteristic features). This defining versus characteristic distinction is combined with a two-stage processing mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
699
3
29

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,240 publications
(764 citation statements)
references
References 38 publications
20
699
3
29
Order By: Relevance
“…Much has been made in the literature (e.g. Smith et al, 1974) about the well-definedness of BIRDS for example. Smith et al used the clear distinction between birds and nonbirds to argue for a distinction between defining features, and merely characteristic features.…”
Section: Discussionmentioning
confidence: 99%
“…Much has been made in the literature (e.g. Smith et al, 1974) about the well-definedness of BIRDS for example. Smith et al used the clear distinction between birds and nonbirds to argue for a distinction between defining features, and merely characteristic features.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1970's, a range of psychological studies has shown for such one-place predicates that subjects consistently rank some instances of a concept as more typical than others, and that such rankings correlate with other measures of typicality such as categorization speed and error rate (e.g. Rosch 1973;Smith et al 1974;Rosch and Mervis 1975). Moreover, I follow Hampton (2007) in assuming that an instance's category membership and its typicality as an instance of that category are two related behavioral measurements, based on one and the same underlying variable.…”
Section: Typicality: Defining Contextmentioning
confidence: 99%
“…true of all members) as well as features that were only characteristic (i.e. true of typical members) (Smith et al, 1974). One of the descriptions presented on a trial contained the necessary features of the target category but not the characteristic ones, whereas the other description contained the characteristic features but not the necessary ones.…”
Section: Studies Demonstrating the Two Categorization Mechanismsmentioning
confidence: 99%